Severity of Subjective Cognitive Complaints and Worries in Older Adults Are Associated With Cerebral Amyloid-β Load - Schwarz, Claudia; Lange, Catharina; Benson, Gloria S.; Horn, Nora; Wurdack, Katharina; Lukas, Mathias; Buchert, Ralph; Wirth, Miranka; Flöel, Agnes (Frontiers in Aging Neuroscience, 2021)
Subjective cognitive decline (SCD) is considered an early risk stage for dementia due to Alzheimer’s Disease (AD) and the development of pathological brain changes, including the aggregation of amyloid-beta (amyloid-β) plaques. This study evaluates the association between specific features of SCD and cerebral amyloid-β load measured by positron emission tomography (PET) with 18F-florbetaben in 40 cognitively normal older individuals. Global amyloid-β, as well as regional amyloid-β load for frontal, temporal, parietal, and cingulate cortex, was quantified. Specific features of SCD, including subjective cognitive complaints and worry, were assessed using the 39-item Everyday Cognition Scales and the 16-item Penn State Worry Questionnaire. Spearman rank partial correlation analyses, adjusted for age and apolipoprotein E ε4 status, were conducted to test for associations between specific features of SCD and cerebral amyloid-β load. Severity of subjective cognitive complaints in everyday memory and organization was positively correlated with amyloid-β load in the frontal cortex. In addition, severity of subjective cognitive complaints in everyday planning was positively correlated with amyloid-β load in the parietal cortex. Higher levels of worry were associated with higher amyloid-β load in the frontal cortex. After correction of PET data for partial volume effects, these associations were reduced to trend level. In conclusion, severity of subjective cognitive complaints and level of trait worry were positively associated with cortical amyloid-β burden, particularly in the frontal and parietal cortex. Further studies are required to elucidate the direction of these associations in order to develop strategies to prevent amyloid deposition and cognitive decline.